Investigating the impact of the COVID-19 pandemic on the nutritional status of infants and toddlers: insights from China - Lijuan Gu; Linsheng Yang; Hairong Li (BMC, 2024)
Abstract Background A comprehensive understanding of the impact of the COVID-19 pandemic on childhood nutrition is crucial for devising effective mitigation strategies. However, existing knowledge regarding the pandemic's effect on childhood nutritional status remains limited. Furthermore, research focusing on young children aged 0-3 years is scarce. Methods Leveraging the outbreak that originated in Wuhan in Dec 2019, the epicenter of China's first and largest outbreak, and national survey and statistical yearbook data, this study conducted a natural experimental analysis with the consideration of geographical exposure, temporal exposure and survey cohort effects to investigate the pandemic's impacts on varying nutritional indicators of infants and toddlers aged 0-36 months. A comprehensive set of sensitivity analyses, robustness checks and falsification tests were conducted. The potential heterogeneities across socioeconomic and age groups were also examined. Results The pandemic was robustly predictive of a higher weight-for-age z-score (WAZ) and length/height-for-age z-score (HAZ), and a lower likelihood of underweight. The effects of the pandemic on increasing WAZ and reducing underweight were more pronounced among children from economically disadvantaged backgrounds or aged 0-12 months. Additionally, the increasing HAZ was primarily among children from households with lower family income. Moreover, the pandemic was negatively linked to the body mass index (BMI)-for-age z-score (BAZ) of children residing in more developed cities, and positively linked to overweight/obesity among children aged 13-24 months. Conclusions This study adds to a more comprehensive understanding of the impact of the COVID-19 pandemic on childhood nutrition. Notably, the findings highlight that weight gain attributable to the pandemic was predominantly among vulnerable children from disadvantaged backgrounds and younger age groups, who were already at a higher risk of overweight/obesity before the pandemic. Consequently, our findings imply the necessity of greater caution to the widened gap in childhood malnutrition post-pandemic. Furthermore, the study emphasizes the importance of implementing adaptable strategies with the consideration of social justice to safeguard all children's right to optimal growth from exogenous shocks and to achieve the children-related SDGs by 2030.